KOMUNIKASI DAKWAH DAN INKLUSI SOSIAL DALAM MASYARAKAT MULTIKULTURAL - Ulfain; Zahrani, Siti (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
The existence of communities composed of diverse ethnic, cultural, and religious backgrounds demands adaptive and inclusive approaches to da'wah communication. This research departs from the reality that the practice of conveying religious messages amid social diversity often generates social tensions rather than strengthening social cohesion. The primary objective of this study is to examine patterns of da'wah communication employed by preachers in fostering social inclusion within multicultural communities, as well as to identify factors that influence its effectiveness. A qualitative approach with a case study design was chosen as the methodological framework, accompanied by data collection through in-depth interviews with twelve selected informants, six months of participatory observation across three multicultural communities in Yogyakarta, and supporting document analysis. The analytical process employed the interactive model of Miles, Huberman, and Saldaña. Findings indicate that da'wah communication grounded in local wisdom values and the principle of rahmatan lil 'alamin consistently strengthens mutual respect among groups. Da'i who adopt dialogical, empathetic, and non-confrontational communication styles proved more successful in building social bridges among diverse communities. Furthermore, the utilization of interfaith public spaces as arenas for da'wah accelerates the process of social integration. These results affirm that inclusive da'wah communication is not merely a religious instrument but also a strategic form of social capital for harmonious pluralistic societies